Negative differential electrical resistance of a rotational organic nanomotor - Sadeghi, Hatef; Sangtarash, Sara; Al-Galiby, Qusiy; Sparks, Rachel; Bailey, Steven; Lambert, Colin J. (Beilstein Journal of Nanotechnology, 2015)
A robust, nanoelectromechanical switch is proposed based upon an asymmetric pendant moiety anchored to an organic backbone between two C60 fullerenes, which in turn are connected to gold electrodes. Ab initio density functional calculations are used to demonstrate that an electric field induces rotation of the pendant group, leading to a nonlinear current–voltage relation. The nonlinearity is strong enough to lead to negative differential resistance at modest source–drain voltages.
Keywords: molecular electronics; molecular switch

(untitled) - Hiratsuka, Y.; Tada, T.; Oiwa, K.; Kanayama, T.; Uyeda, T. Q. P. (Biophys. J., 2001)

(untitled) - van den Heuvel, M. G.; Dekker, C. (Science, 2007)

(untitled) - Fujimoto, K.; Kitamura, M.; Yokokawa, M.; Kanno, I.; Kotera, H.; Yokokawa, R. (ACS Nano, 2012)

(untitled) - Aoyama, S.; Shimoike, M.; Hiratsuka, Y. (Proc. Natl. Acad. Sci. U. S. A., 2013)

(untitled) - Taira, S.; Du, Y.-Z.; Hiratsuka, Y.; Uyeda, T. Q. P.; Yumoto, N.; Kodaka, M. (Biotechnol. Bioeng., 2008)

(untitled) - Song, W.; Möhwald, H.; Li, J. (Biomaterials, 2010)

(untitled) - Ionov, L.; Stamm, M.; Diez, S. (Nano Lett., 2005)

(untitled) - van den Heuvel, M. G. L.; de Graaff, M. P.; Dekker, C. (Science, 2006)

(untitled) - Hess, H.; Clemmens, J.; Howard, J.; Vogel, V. (Nano Lett., 2002)

(untitled) - Bachand, G. D.; Hess, H.; Ratna, B.; Satir, P.; Vogel, V. (Lab Chip, 2009)

(untitled) - Fischer, T.; Agarwal, A.; Hess, H. (Nat. Nanotechnol., 2009)

(untitled) - Schliwa, M.; Woehlke, G. (Nature, 2003)

(untitled) - Bruns, C. J.; Stoddart, J. F. (Acc. Chem. Res., 2014)

(untitled) - Kumar, K. R. S.; Kamei, T.; Fukaminato, T.; Tamaoki, N. (ACS Nano, 2014)

(untitled) - Gao, W.; Wang, J. (Nanoscale, 2014)

(untitled) - Browne, W. R.; Feringa, B. L. (Nat. Nanotechnol., 2006)

Molecular devices and machines: concepts and perspectives for the nanoworld - Balzani, V.; Credi, A.; Venturi, M. (John Wiley & Sons, Inc., 2008)

(untitled) - Garcia-Garibay, M. A. (Proc. Natl. Acad. Sci. U. S. A., 2005)

Molecular Machines - Karlen, S. D.; Garcia-Garibay, M. A. (Amphidynamic crystals: Structural blueprints for molecular machines, 2005)

(untitled) - Davis, A. P. (Angew. Chem., Int. Ed., 1998)

(untitled) - Kelly, T. R.; Sestelo, J. P.; Tellitu, I. (J. Org. Chem., 1998)

(untitled) - Hugel, T.; Holland, N. B.; Cattani, A.; Moroder, L.; Seitz, M.; Gaub, H. E. (Science, 2002)

(untitled) - Liu, Y.; Flood, A. H.; Bonvallet, P. A.; Vignon, S. A.; Northrop, B. H.; Tseng, H.-R.; Jeppesen, J. O.; Huang, T. J.; Brough, B.; Baller, M.; Magonov, S.; Solares, S. D.; et al. (J. Am. Chem. Soc., 2005)

(untitled) - Coskun, A.; Banaszak, M.; Astumian, R. D.; Stoddart, J. F.; Grzybowski, B. A. (Chem. Soc. Rev., 2012)

(untitled) - Bruns, C. J.; Stoddart, J. F. (Nat. Nanotechnol., 2013)

(untitled) - Morin, J.-F.; Shirai, Y.; Tour, J. M. (Org. Lett., 2006)

(untitled) - Cumings, J.; Zettl, A. (Science, 2000)

(untitled) - Yu, M.-F.; Yakobson, B. I.; Ruoff, R. S. (J. Phys. Chem. B, 2000)

(untitled) - Kolmogorov, A. N.; Crespi, V. H. (Phys. Rev. Lett., 2000)

(untitled) - Zheng, Q.; Jiang, Q. (Phys. Rev. Lett., 2002)

(untitled) - Forró, L. (Science, 2000)

(untitled) - Williams, P. A.; Papadakis, S. J.; Patel, A. M.; Falvo, M. R.; Washburn, S.; Superfine, R. (Phys. Rev. Lett., 2002)

(untitled) - Rivera, J. L.; McCabe, C.; Cummings, P. T. (Nano Lett., 2003)

(untitled) - Sangtarash, S.; Sadeghi, H.; Ahmadi, M. T.; Ghadiry, M. H.; Anwar, S.; Ismail, R. (J. Comput. Theor. Nanosci., 2012)

(untitled) - Grace, I. M.; Bailey, S. W.; Lambert, C. J. (Phys. Rev. B, 2004)

(untitled) - Bailey, S. W. D.; Amanatidis, I.; Lambert, C. J. (Phys. Rev. Lett., 2008)

(untitled) - Cai, K.; Yin, H.; Qin, Q. H.; Li, Y. (Nano Lett., 2014)

(untitled) - Fennimore, A. M.; Yuzvinsky, T. D.; Han, W.-Q.; Fuhrer, M. S.; Cumings, J.; Zettl, A. (Nature, 2003)

(untitled) - Bourlon, B.; Glattli, D. C.; Miko, C.; Forró, L.; Bachtold, A. (Nano Lett., 2004)

(untitled) - Niguès, A.; Siria, A.; Vincent, P.; Poncharal, P.; Bocquet, L. (Nat. Mater., 2014)

(untitled) - Leary, E.; González, M. T.; van der Pol, C.; Bryce, M. R.; Filippone, S.; Martín, N.; Rubio-Bollinger, G.; Agraït, N. (Nano Lett., 2011)

(untitled) - Soler, J. M.; Artacho, E.; Gale, J. D.; García, A.; Junquera, J.; Ordejón, P.; Sánchez-Portal, D. (J. Phys.: Condens. Matter, 2002)

(untitled) - Dion, M.; Rydberg, H.; Schröder, E.; Langreth, D. C.; Lundqvist, B. I. (Phys. Rev. Lett., 2004)

(untitled) - Langreth, D. C.; Dion, M.; Rydberg, H.; Schröder, E.; Hyldgaard, P.; Lundqvist, B. I. (Int. J. Quantum Chem., 2005)

(untitled) - Landauer, R. (Z. Phys. B: Condens. Matter, 1987)

(untitled) - Ferrer, J.; Lambert, C. J.; García-Suárez, V. M.; Manrique, D. Zs.; Visontai, D.; Oroszlany, L.; Rodríguez-Ferradás, R.; Grace, I.; Bailey, S. W. D.; Gillemot, K.; Sadeghi, H.; Algharagholy, L. A. (New J. Phys., 2014)

(untitled) - Sadeghi, H.; Mol, J. A.; Lau, C. S.; Briggs, G. A. D.; Warner, J.; Lambert, C. J. (Proc. Natl. Acad. Sci. U. S. A., 2015)

(untitled) - Lambert, C. (Chem. Soc. Rev., 2015)

(untitled) - Martín, S.; Manrique, D. Zs.; García-Suárez, V. M.; Haiss, W.; Higgins, S. J.; Lambert, C. J.; Nichols, R. J. (Nanotechnology, 2009)

(untitled) - Sadeghi, H.; Sangtarash, S.; Lambert, C. J. (Beilstein J. Nanotechnol., 2015)

(untitled) - Mol, J. A.; Lau, C. S.; Lewis, W. J. M.; Sadeghi, H.; Roche, C.; Cnossen, A.; Warner, J. H.; Lambert, C. J.; Anderson, H. L.; Briggs, G. A. D. (Nanoscale, 2015)

(untitled) - Prins, F.; Barreiro, A.; Ruitenberg, J. W.; Seldenthuis, J. S.; Aliaga-Alcalde, N.; Vandersypen, L. M. K.; van der Zant, H. S. J. (Nano Lett., 2011)